On The Study Of The Dynamics Of The Zvs Three-phase Dc/dc Converter - Demercil S. Oliveira Jr.; René P. T. Bascopé; Ivo Barbi; Carlos E. A. Silva (Eletrônica de Potência)
This paper presents the theoretical analysis concerning the operating stages of the three-phase dc/dc converter associated with the hybridge rectifier, in order to obtain its dynamic model. The nonlinear instant model in state space form is obtained by the definition of a switching function q(t). From this model, an average nonlinear model is proposed, as well as a linearized model. The dynamic model, the controller design, and also experimental results obtained from a prototype of 6kW are presented.